Inquiry-Based Activities with Woodlice in Early Childhood Education - Isabel García-Rodeja; Sara Barros; Vanessa Sesto (MDPI AG, 2024)
This study aims to describe the implementation of a teaching sequence where preschool-age children participate in activities related with woodlice. Although there is extensive literature on inquiry-based activities, most studies have been conducted in higher educational stages. Data were collected though audio and video recordings of the sessions, which have then been transcribed. The children participated in research activities in which they had no difficulty in posing hypotheses and making predictions. In relation to the experimental design, we observed difficulties in understanding the purpose of the experiment and how to reach conclusions from the experimental results. From the results of this study, we can conclude that children from an early age can engage in inquiry activities where they are given opportunities to make predictions, formulate hypotheses, and, with the help of the teacher, plan simple experiments to test their ideas.